Avaliação do desempenho de ferramentas de metal duro e cermet no torneamento do aço ABNT 1045 - Guilherme Souza Aleixo (2020)
The turning machining is one of the most used operations in the metal-mechanical industry, ensuring high standard patterns of finish and tight margin of tolerability. In this sense, a machine tool, the cutting parameters, as well as the tool used, are key elements for the application of optimal production standards. The aim of this dissertation is to study the effect of the variation of the input parameters cutting speed (200, 250 e 300 m/min), feed (0,1 e 0,2 mm/rev), tool material (carbide and cermet) and chip break geometry on the output parameters (machined surface roughness, chip shape, chip thickness ratio and tool wear) in dry turning of AISI 1045 steel. The results indicated that as far as the surface roughness is concerned, feed is the only significant factor, however, chip breaker geometry also has influence, since the roughness behavior for the finishing chip breaker (FP) was similar. Regarding chip shape, the highest level of feed generated chips with the highest thickness and that the tool material was influential on the chip shape. The chip thickness ratio decreased as the cutting speed and feed increased. Finally, it can be seen that the predominant wear mechanism was adhesion and the tool with the best performance was the cemented carbide with FP chip breaker. It was not possible to establish a relationship between roughness maximum flank wear.